2007
DOI: 10.1603/0022-2585(2007)44[530:hpitsu]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Human Plague in the Southwestern United States, 1957–2004: Spatial Models of Elevated Risk of Human Exposure to <I>Yersinia pestis</I>

Abstract: Plague is a rare but highly virulent flea-borne zoonotic disease caused by the Gram-negative bacterium Yersinia pestis Yersin. Identifying areas at high risk of human exposure to the etiological agent of plague could provide a useful tool for targeting limited public health resources and reduce the likelihood of misdiagnosis by raising awareness of the disease. We created logistic regression models to identify landscape features associated with areas where humans have acquired plague from 1957 to 2004 in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…However, 11% of case homes were situated in areas classified as low risk. We assumed that, similar to other plague foci, 17,18,[44][45][46][47] most plague cases occur in the peridomestic setting. This finding was supported by the observation that a higher proportion of case homes, relative to controls, were located within pixels classified as elevated risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 11% of case homes were situated in areas classified as low risk. We assumed that, similar to other plague foci, 17,18,[44][45][46][47] most plague cases occur in the peridomestic setting. This finding was supported by the observation that a higher proportion of case homes, relative to controls, were located within pixels classified as elevated risk.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic Information Systems (GIS) and Remote Sensing (RS) technology coupled with statistical modeling have been useful in generating risk maps that display this spatial heterogeneity and such outputs may aid in identifying previously uncharacterized plague foci. [17][18][19][20][21][22] In recent decades, most human plague infections have been reported from eastern Africa and Madagascar. 16,23 The GISbased models have identified widespread areas of risk on the African continent, and they have determined that ecological predictors of risk are variable among these foci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 Seasonal trends in flea infestation by host species and district ated with domestic or peridomestic settings. [27][28][29][30][31][32] Furthermore, because of their high vector efficiency, broad host preferences, and close association with human dwellings, X. cheopis and X. brasiliensis have been implicated as primary vectors to humans in domestic and peridomestic settings. 7,10,19 Because of the high abundance of R. rattus infested with X. cheopis or X. brasiliensis in and around human dwellings in Arua and Nebbi districts, respectively, it is likely that, during epizootic periods when a high proportion of these fleas may be infected with Y. pestis , domestic and peridomestic areas pose the greatest risk to humans.…”
Section: Discussionmentioning
confidence: 99%
“…37 In the western United States, a geographical information system (GIS) -based model indicated that suitability for plague increases for elevations up to 2,129 m but declines at higher elevations. 38 Besides elevation, plague occurrences seem to be linked to seasonal vegetation changes, resulting from rainfall variability through the year, and to moderate EVI values and reasonably high seasonality, suggesting that forests are not suitable for plague; however, because people do not frequently live in the forests, this conclusion could be misleading.…”
Section: Discussionmentioning
confidence: 99%